1989
DOI: 10.1080/09853111.1989.11105185
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic framework of the thrust geometry and structural inversion in the southeastern Pyrenees : La Garrotxa area

Abstract: antiformai stacks frprf'Sf'nts an inVf'fSion of prf'-f"xistent f"xtensionai faults whi('h formt'd half-~rabpn ~t'onH'lries. Thp basenlPnl ro('ks im olwd in thp structurI' rI'prt'st'nl short-culs fornwd in th!' foolwall of Iht' t'xlpnsional faults. All thrusts of La Carrotxa I:lrf'a branch with thp UppPf Garrotxa thrust. Thl' mort-' complex structure of La Garrotxa area than the adjac('nt areas within thp Cadi unit. is duf' to the initial complf'x synst'dimentary ~f'omf'lry of the sedimentary pile, TIlt' Cadi u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…Therefore, those extensional features (LowerMiddle Santonian in age) described in this study, as well as the ones reported by Martínez et al (1989) and Pujadas et al (1989), are parallel to major thrusts, and the age relationship indicates that they were developing in front of advancing thrust sheets. At that time continental collision was already taking place between the Iberian and European plates.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Therefore, those extensional features (LowerMiddle Santonian in age) described in this study, as well as the ones reported by Martínez et al (1989) and Pujadas et al (1989), are parallel to major thrusts, and the age relationship indicates that they were developing in front of advancing thrust sheets. At that time continental collision was already taking place between the Iberian and European plates.…”
Section: Discussionmentioning
confidence: 53%
“…2. Inversion of Upper Cretaceous to Paleocene halfgrabens (Martínez et al 1989;Pujadas et al 1989; and the present paper) developed during compression, when the Pyrenean collision was already taking place.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Dotted red line shows the southern termination of the Upper Cuisian–Lutetian evaporites according to Martínez et al . (). Black line corresponds to the structural cross‐section A–A’ in (C).…”
Section: Introductionmentioning
confidence: 99%
“…Cette organisation structurale montre l'existence, dans la Zone Axiale orientale, d'une importante phase de raccourcissement NNE-SSW post-garumnienne. La plupart des auteurs (Aschauer 1934;Estévez 1968;Papa 1984;Martinez et al 1989) s'accordent à associer le chevauchement des Aspres à certaines unités allochtones du versant Sud des Pyrénées (Zone Sud-Pyrénéenne), les klippes de Coustouges et de Bac-Grillera notamment (Fig. 2), dont la mise en place s'est effectuée, vraisemblablement, au Cuisien supérieur et au Lutétien inférieur.…”
Section: Cadre Géologiqueunclassified